Is the Public Sector Comparator Right for Developing Countries? Appraising Public-Private Projects in Infrastructure - Leigland, James (World Bank, Washington, DC, 2012)
African officials have shown new interest in infrastructure projects involving private participation. But with so little experience with such projects, these officials often have limited knowledge about how best to assess their value for money. Some experts have suggested that developing countries use the method centering on the public sector comparator. But this method has come under criticism in some industrial countries. The debate about its use in the industrial world raises questions about whether it is appropriate in developing countries. This paper discusses: how the method works; what the problems are; what the U.K. reforms do; and what about developing countries.